Transformative Islamic Theology as a Framework of Integrative-Holistic Tawhid: A Reconstruction of the Paradigm of Religiosity, Social Justice, and Public Ethics in Contemporary Muslim Society - Silfia Marta Maulidya; Ahmad Rifki Abdillah; Halimatus Sadiyah; Ali Hasan Siswanto (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The epistemological crisis in contemporary Islamic theological studies is marked by the dominance of normative-dogmatic theology detached from social reality, resulting in the privatization of spirituality, fragmentation of public ethics, and theology’s inability to respond to problems of injustice, economic dehumanization, and the degradation of political ethics. Amid this situation, there exists a research gap in the absence of a theological framework capable of integrating spiritual, psychological, and social dimensions holistically. Islamic theological literature—both classical and contemporary—has rarely elaborated the relationship between transformative theology and an integrative tawhid-based counseling approach, even though this approach offers significant potential to renew the way society understands and practices religiosity. This study develops a framework of Transformative Islamic Theology through an Integrative-Holistic Tawhid approach by combining theological analysis, practical philosophy, and perspectives from spiritual psychology. The method employed is a conceptual-critical study using hermeneutic and constructive analysis of primary literature and recent scholarly works. This article argues that tawhid, when defined as an awareness of ontological and ethical unity, is not merely the foundation of individual faith, but also a practical force that shapes social ethics, political behavior, and justice-oriented economic orientation.